Diversity in Natural Transformation Frequencies and Regulation across Vibrio Species - Simpson, Chelsea A. (mBio, 2019)
In Vibrio species, chitin-induced natural transformation enables bacteria to take up DNA from the external environment and integrate it into their genome. Expression of the master competence regulator TfoX bypasses the need for chitin induction and drives expression of the genes required for competence in several Vibrio species. Here, we show that TfoX expression in Vibrio campbellii strains DS40M4 and NBRC 15631 enables high natural transformation frequencies. Conversely, transformation was not achieved in the model quorum-sensing strain V. campbellii BB120 (previously classified as Vibrio harveyi). Surprisingly, we find that quorum sensing is not required for transformation in V. campbellii DS40M4 or Vibrio parahaemolyticus in contrast to the established regulatory pathway in Vibrio cholerae in which quorum sensing is required to activate the competence regulator QstR. Similar to V. cholerae, expression of both QstR and TfoX is necessary for transformation in DS40M4. There is a wide disparity in transformation frequencies among even closely related Vibrio strains, with V. vulnificus having the lowest functional transformation frequency. Ectopic expression of both TfoX and QstR is sufficient to produce a significant increase in transformation frequency in Vibrio vulnificus. To explore differences in competence regulation, we used previously studied V. cholerae competence genes to inform a comparative genomics analysis coupled with transcriptomics. We find that transformation capability cannot necessarily be predicted by the level of gene conservation but rather correlates with competence gene expression following TfoX induction. Thus, we have uncovered notable species- and strain-level variations in the competence gene regulation pathway across the Vibrio genus.